Inundation zones, jordan river and the vega, Tunja (Revista Cientifica Ingenio Magno, 2020)
This article addresses the problem of flooding in the city of Tunja from the registration of key information, until 2016, of the Jordan and La Vega rivers on their tour of the city (approx. 11.5 kilometers). The conditions in which the sections of each river were located in terms of efficiency in fluid conduction, presence of waste, livestock and channeling are observed. Likewise, this register includes the identification of the main vehicle and pedestrian passage structures and the direct pours that are in its route. The general state in which the rivers were found showed poor coexistence of the city with them, and a contamination of the water resource translated into the presence of mosquitoes, bad smells, cattle within the riverbed, was evident, thick vegetation, presence of debris of considerable size, of heavy passing structures that failed in previous winter waves and invasion of its round.
Keywords: Flood zones; emergency; hydrological model; hydraulic model